Values and professional identity of student-age population - I. A. Koch; В. A. Orlov (Russian State Vocational Pedagogical University, 2020)
Introduction. Profound social transformations in the Russian society, the formation of market relations have led to the deformation of the system of life values among the citizens of the country. Changes in value orientations directly affect the professional identity of new generations. This circumstance requires new forms of work on professional guidance of young people, taking into account their attitudes, as well as unstable labour market conditions.The aim of the present research is to investigate social conditions and values-orientations, which influence the choice of professional niche and employment of students, who pursue higher education.Methodology and research methods. The initial methodological framework is based on axiological and activity-based approaches, as well as sociology of professions. The main empirical methods of sociological research involve observation and mass questionnaire survey of students of Ural State Mining University (Ekaterinburg) and Ural Institute of Management of the Russian Presidential Academy of National Economy and Public Administration (Ekaterinburg). 606 full-time students were interviewed.Results and scientific novelty. The value structure and professional preferences of young people transformed by external causes, their recognition of the acquired profession and their role in the implementation of their own life plans were analysed in a comprehensive manner. It was revealed that half of the respondents made a conscious choice for the profile of university education and they are going to pursue the occupations for which they are qualified. One third of respondents consider their choice as spontaneous and random, and every fifth respondent is ready for any employment. For many respondents, the question of the relationship between future work and the education received remains open, which partly reflected the need driven by the Russian society to receive a diploma acquired at a higher education institution.The social factors influencing the choice of profession and professional self-determination of students are revealed, the main of which are the following: interesting work and popularity of the profession. Choosing his or her profession, every second student is confident that it will be associated with interesting work, which for many of them is one of the key life priorities (42.2%). According to young people, the prestige of profession is very significant and can be expressed in high wages and in demand in the labour market. Among the prestigious professions are doctors, engineers, lawyers, entrepreneurs and civil servants. The majority of students consider their specialty to be prestigious and in-demand. According to every third student, a prestigious job gives a high social status and requires high qualifications to perform it. One third of respondents are confident that it will give them the opportunity to build a career and to become the holders of high social status; thus, the students understand that it is necessary to acquire high qualification and to have individual abilities and skills for the future profession. The fourth part of respondents believe that their future work would help them to realise their potential. At the same time, every sixth student (15.6%) expressed a desire to change the direction of training, which indicates disappointment in profession or initially wrong choice.It is concluded that professional identity of young people is determined by individualistic, conformistic values and motivation for self-affirmation.Practical significance. The research material and results can be employed to organise the pedagogical support for the process of professionalism of university students and to develop the recommendations for vocational guidance work among schoolchildren, college students and young workers.